Low 25-Hydroxyvitamin D Concentrations and Risk of Incident Cognitive Impairment in Black and White Older Adults: The Health ABC Study. Issue 1 (2nd January 2018) - Kilpatrick, Laurel; Houston, Denise K.; Wilson, Valerie K.; Lovato, James; Ayonayon, Hilsa N.; Cauley, Jane A.; Harris, Tamara; Simonsick, Eleanor M.; Yaffe, Kristine; Kritchevsky, Stephen B.; Sink, Kaycee M.
ABSTRACT: Using data from the Health, Aging, and Body Composition study, we examined whether low 25-hydroxyvitamin D (25[OH]D) concentrations were associated with prevalent or incident cognitive impairment. Serum 25(OH)D concentrations were measured in 2, 786 older adults and categorized as <20 ng/mL, 20 to <30 ng/mL, or ≥30 ng/mL. Cognitive impairment was defined as a score >1.5 standard deviations below race and education specific means on either digit symbol substitution test or modified mini-mental state test. Logistic regression determined the odds of cognitive impairment at baseline and year 5 by 25(OH)D category. 25(OH)D concentrations were <30 ng/mL in 57.3% of whites and 84.6% of blacks. After excluding participants with baseline cognitive impairment ( n = 340), 13% of whites and 13% of blacks developed cognitive impairment by year 5. In whites, 25(OH)D concentrations <30 ng/mL were not associated with prevalent or incident cognitive impairment. Black participants with 25(OH)D concentrations <20 ng/mL had a higher odds of prevalent, but not incident cognitive impairment (OR (95% CI): 2.05 (1.08–3.91), p = 0.03) compared to participants with 25(OH)D concentrations ≥30 ng/mL. Low 25(OH)D concentrations were associated with twofold higher odds of prevalent cognitive impairment in blacks.